2014
DOI: 10.3109/08820139.2014.936445
|View full text |Cite
|
Sign up to set email alerts
|

The frequency of Th17 and Th22 cells in patients with colorectal cancer at pre-operation and post-operation

Abstract: T helper 17 (Th17) and Th22 cells regulate the development of tumors. However, their roles in the development of colorectal cancer (CRC) are still unclear. A total of 49 patients with CRC and 18 healthy controls (HC) were evaluated for the percentages of circulating Th17 and Th22 cells by flow cytometry. The concentrations of serum interleukin-17A (IL-17A), IL-22 and carcinoembryonic antigen (CEA) were examined. The levels of IL-17A and IL-22 in tumors were determined by real-time PCR. We found that the percen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
27
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(30 citation statements)
references
References 30 publications
2
27
1
Order By: Relevance
“…29 Another report showed that Th17 and Th22 cells were higher in CRC tissues and were negatively correlated with tumor progression. 31 The levels of IL22 and IL17 transcripts were also significantly higher in early stages of CRC, compared with advanced stages. 31 Interestingly, after tumor resection, their levels were significantly increased in patients with advanced stages.…”
Section: Discussionmentioning
confidence: 93%
“…29 Another report showed that Th17 and Th22 cells were higher in CRC tissues and were negatively correlated with tumor progression. 31 The levels of IL22 and IL17 transcripts were also significantly higher in early stages of CRC, compared with advanced stages. 31 Interestingly, after tumor resection, their levels were significantly increased in patients with advanced stages.…”
Section: Discussionmentioning
confidence: 93%
“…In particular, CD45RO + memory T lymphocytes, cytotoxic CD8 + T cells (CTLs) and interferon (IFN)-γ-producing T helper1 cells (Th1) have been found to be associated with prolonged survival in CRC, irrespective of tumor stage ( 6 8 ), while the role of Th2 cells in colon cancer is mainly harmful as IL-4 directly and indirectly favors tumor growth ( 9 11 ). CD4 + T cells are now known to differentiate into additional effector T-cell subsets (i.e., Th17, Th9, follicular helper T, Th22) with contrasting and unclear roles in the development of CRC ( 12 14 ) as well as immunosuppressive cells, like exhausted, anergic/tolerant, and subsets of regulatory T cells (Tregs) that can favor cancer progression ( 15 18 ). In fact, the CD4 + CD25 + Foxp3 + Tregs subpopulation may exert a critical role in cancer promotion ( 19 , 20 ).…”
Section: Introductionmentioning
confidence: 99%
“…We and others have shown a higher frequency of IL-17-producing T cell populations, including MAIT cells and gd T cells, in tumor versus adjacent bowel tissue. [9][10][11][12][13][14] Differences in the frequency of regulatory T cells (Tregs) have also been observed, 10,11 but the effect of the function of these T cell populations on other infiltrating T cells is not clear. We hypothesized that T cells in tumor tissue would have impaired cytokine production and proliferative ability due to the suppressive environment in CRC tumors.…”
Section: Introductionmentioning
confidence: 99%